2017
DOI: 10.1021/acschembio.7b00001
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Aptamer Discovery through Apta-Seq and Its Application to ATP Aptamers Derived from Human-Genomic SELEX

Abstract: Laboratory-evolved RNAs bind a wide variety of targets and serve highly diverse functions, including as diagnostic and therapeutic aptamers. The majority of aptamers have been identified using in vitro selection (SELEX), a molecular evolution technique based on selecting target-binding RNAs from highly diverse pools through serial rounds of enrichment and amplification. In vitro selection typically yields multiple distinct motifs of highly variable abundance and target-binding affinities. The discovery of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…RT stop sites are mapped using ShapeFinder, a package used to quantitatively map RT stops at nucleotide resolution and when a ligand titration is used, the stops uncover RNA conformational changes due ligand binding (Vasa, Guex, Wilkinson, Weeks, & Giddings, 2008). When this method was applied to a human-genomic in vitro selection for ATP-binders, it revealed three novel humangenome-derived ATP-binding RNA aptamers, and confirmed the existence of two previously identified aptamers (Abdelsayed et al, 2017;Vu et al, 2012). These results demonstrated the robustness of the method to perform structural analysis in a high-throughput pipeline and allowed determination of dissociation rate constants, K D s, for selected pools while eliminating single-clone biochemical assessment.…”
Section: High-throughput Characterization Methodsmentioning
confidence: 65%
See 3 more Smart Citations
“…RT stop sites are mapped using ShapeFinder, a package used to quantitatively map RT stops at nucleotide resolution and when a ligand titration is used, the stops uncover RNA conformational changes due ligand binding (Vasa, Guex, Wilkinson, Weeks, & Giddings, 2008). When this method was applied to a human-genomic in vitro selection for ATP-binders, it revealed three novel humangenome-derived ATP-binding RNA aptamers, and confirmed the existence of two previously identified aptamers (Abdelsayed et al, 2017;Vu et al, 2012). These results demonstrated the robustness of the method to perform structural analysis in a high-throughput pipeline and allowed determination of dissociation rate constants, K D s, for selected pools while eliminating single-clone biochemical assessment.…”
Section: High-throughput Characterization Methodsmentioning
confidence: 65%
“…High-throughput methods that incorporate biochemical assessment of individual sequences decrease the time requirement of aptamer identification and increases the likelihood of uncovering larger diversity of functional sequences. Current methods have been used to uncover human ATP-binding RNA aptamers, analyze MS2 aptamers, and identify CRISPR-Cas complex specificity (Abdelsayed et al, 2017;Buenrostro et al, 2014;Jung et al, 2017). These techniques are valuable in the advancement of in vitro selection and aid in understanding of the evolution of functional RNAs from random sequence space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major interaction forces in the binding process are defined to be hydrogen bond and charge-charge interaction that are provided from native phosphodiester polymeric linker and the bases on loops. [27][28][29][30] The concept of aptamer ligands binding to proteins was reported early 1980s for the study of human immunodeficiency virus (HIV) and adenovirus. 31,32 In this investigation it had shown that the viruses have a high force of affinity and specificity for the encoding of small numbers of RNAs that bind to viruses or cellular proteins.…”
Section: Conventional Structurementioning
confidence: 99%